RESOLUTION OF THYROTOXICOSISASSOCIATED SEVERE PULMONARY HYPERTENSION WITH TREATMENT OF THYROTOXICOSIS: A CASE REPORT - Nordin, Hidayatil Alimi Bin Keya; Jeevaraj, Lavanya; Rahmatullah, Ijaz Bt Hallaj; Rahim , Anilah Binti Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Pulmonary hypertension among pregnant women carries high mortality for the mother and fetus. Pulmonary hypertension has been associated with thyrotoxicosis. We report a case of reversible severe pulmonary hypertension secondary to thyrotoxicosis in a 35-year-old pregnant female, who was diagnosed with Graves’ disease in 2019. She was admitted for thyroid storm at 12 weeks of gestation [Free T4 59 (9-19), TSH <0.008 (0.35 - 4.94)]. She was treated as per thyroid storm management. A holosystolic murmur was heard at the left sternal edge. Initial echocardiogram showed severe tricuspid regurgitation with pulmonary artery systolic pressure (PASP 73 mmHg). The patient wished to continue with pregnancy despite counseling for termination of pregnancy. She was subsequently followed up by a multidisciplinary team. During the third trimester, T4 was 21 and TSH was <0.008. Repeat 2D-echocardiogram at 36 weeks of pregnancy showed resolution of severe tricuspid regurgitation and pulmonary hypertension (PASP 15 mmHg). She successfully delivered at 36 weeks of pregnancy.